Paediatric innovation in Pakistan: our experience and a call to action. Issue 10 (26th May 2017) - Farooqi, Walid; Subhani, Faysal; Mian, Asad
Abstract : Standardisation in paediatric medicine may have the unintended effect of stifling innovation. Thinking outside the box becomes even more important in low-income to middle-income countries like Pakistan, where a large paediatric population requires healthcare. In addition, there is always a lack of funds, making an innovative, low-cost and high impact solution all the more necessary. While regulation and formal research is an integral part of the process, the local synthesis of a solution must start with a creative idea. To address the dearth of avenues promoting lateral thinking relevant to biomedicine and healthcare among students and faculty, the Critical Creative Innovative Thinking forum was formed at the Aga Khan University in Karachi, Pakistan, by a group consisting of students and faculty in 2014. The primary objective of the forum was to provide an arena conducive to lateral thinking and to equip biomedical professionals with the skill set to enable and promote creativity and innovation. This paper seeks to outline those efforts and discuss their potential impact on paediatric care for resource-limited settings.